Burden and patient characteristics associated with repeat consultation for unscheduled care within 30 days in primary care: a retrospective case control study with implications for aging and public health - Richard, Valentin; Bouazzi, Leila; Richard, Clément; Sanchez, Stéphane (Frontiers in Public Health, 2023)
Introduction Repeated consultations in primary care represent a significant burden on healthcare services. Characterizing the patients who repeatedly attend ambulatory care would enhance our understanding of the healthcare needs of this population, with a view to providing appropriate services. The aim of this study was therefore to identify the factors associated with repeated consultation in unscheduled care. Our secondary aim was to explore the specific profile of patients aged >65 years. Methods A retrospective case–control study comparing re-consultation within 30 days at a primary care facility versus non-reconsulting patients, defined as those who did not reconsult within 30 days, among patients consulting over a period of 1 year (1 January to 31 December 2019). Data was collected for a random sample of 5,059 consultations. Patients and controls were matched for age ± 5 years, and sex. Results The main factors associated with repeat consultation were an initial consultation late at night (midnight to 6.00 am; OR 1.31, 95%CI 1.20–1.44), and psychological disorders as the main diagnosis (OR 1.33, 95%CI 1.20–1.48). Conversely, consulting at the weekend was associated with a lower likelihood of repeat consultation (OR 0.82, 95% 0.85–0.91). Conclusion 30-day reconsultations were significantly more frequent after late night consultation. This could be used as an indicator of the quality of care to assess performance of general practice teams with implications for improving overall health of an aging population.